1998
DOI: 10.1073/pnas.95.12.6876
|View full text |Cite
|
Sign up to set email alerts
|

A human homolog of the Saccharomyces cerevisiae REV3 gene, which encodes the catalytic subunit of DNA polymerase ζ

Abstract: To get a better understanding of mutagenic mechanisms in humans, we have cloned and sequenced the human homolog of the Saccharomyces cerevisiae REV3 gene. The yeast gene encodes the catalytic subunit of DNA polymerase , a nonessential enzyme that is thought to carry out translesion replication and is responsible for virtually all DNA damage-induced mutagenesis and the majority of spontaneous mutagenesis. The human gene encodes an expected protein of 3,130 residues, about twice the size of the yeast protein (1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
207
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(213 citation statements)
references
References 34 publications
5
207
0
1
Order By: Relevance
“…RNA was harvested from p53 ϩ/ϩ and p53 Ϫ/Ϫ HCT116 cells after exposure to 0.02% O 2 or 0.3 g/ml adriamycin and assayed by qRT-PCR. We found that REV3L, the human homolog of the catalytic subunit of DNA polymerase (18), is induced by DNA damage (Fig. 4 and 5B).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…RNA was harvested from p53 ϩ/ϩ and p53 Ϫ/Ϫ HCT116 cells after exposure to 0.02% O 2 or 0.3 g/ml adriamycin and assayed by qRT-PCR. We found that REV3L, the human homolog of the catalytic subunit of DNA polymerase (18), is induced by DNA damage (Fig. 4 and 5B).…”
Section: Resultsmentioning
confidence: 92%
“…8). An induced gene of particular interest was REV3L, the catalytic subunit of DNA polymerase (18). Although p53-dependent induction is not as high as it is for genes like p21, a two-to threefold increase of a key DNA repair enzyme may have profound consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using small interfering RNA on mammalian TLS polymerases have shown that Rev1 and Rev3, but not Pol , are clearly required in UV-induced mutagenesis (9,19,20,26,35). However, it is currently unknown what kind of mechanism is involved in the observed hypermutability of XP-V cells.…”
Section: Role For Pol In Prevention Of Uv-induced Mesenchymal Tumorsmentioning
confidence: 99%
“…Rev1, Rev3 and Rev7 were originally identified in S. cerevisae as being required for mutations induced by most DNA damaging agents [15]. A similar requirement has also been found in human cells [16,17]. This implies that they are involved in TLS, often inserting the "wrong" bases.…”
Section: Tls Polymerasesmentioning
confidence: 94%